Mutations in surface‐sensing receptor WspA lock the Wsp signal transduction system into a constitutively active state. (20th September 2021) - Xu, Anming; Wang, Di; Wang, Yunhao; Zhang, Li; Xie, Zhensheng; Cui, Yifan; Bhamse, Pramod; Yu, Haiying; Zhang, Xue‐Xian; Li, Defeng; Ma, Luyan Z.
Summary: Pseudomonas aeruginosa rugose small‐colony variants (RSCVs) are frequently isolated from chronic infections, yet, they are rarely reported in environmental isolates. Here, during the comparative genomic analysis of two P . aeruginosa strains isolated from crude oil, we discovered a spontaneous in‐frame deletion, wspA Δ280–307, which led to hyper‐biofilm and RSCV phenotypes. WspA is a homologue of methyl‐accepting chemotaxis proteins (MCPs) that senses surfaces to regulate biofilm formation by stimulating cyclic‐di‐guanosine monophosphate (c‐di‐GMP) synthesis through the Wsp system. However, the methylation sites of WspA have never been identified. In this study, we identified E280 and E294 of WspA as methylation sites. The wspA Δ280–307 mutation enabled the Wsp system to lock into a constitutively active state that is independent of regulation by methylation. The result is an enhanced production of c‐di‐GMP. Sequence alignment revealed three conserved repeat sequences within the amino acid residues 280–313 (aa280–313) region of WspA homologues, suggesting that a spontaneous deletion within this DNA encoding region was likely a result of intragenic recombination and that similar mutations might occur in several related bacterial genera. Our results provide a plausible explanation for the selection of RSCVs and a mechanism to confer a competitive advantage for P . aeruginosa in a crude‐oil environment.